Seasonality of Phytoplankton productivity of the river Turag of Dhaka in relation to its water quality (Bangladesh Journal of Botany, 2014)
A total of 16 water quality parameters together with the phytoplankton biomass as chlorophyll a and potential primary productivity of the river Turag of Bangladesh were measured for one year (July 1994 - June 1995). Potential primary productivity ranged from 6.22 - 199.7 ?gC/l/hr which showed a closer peak with total phytoplankton. Chlorophyll a, phosphate-phosphorus and nitrate-nitrogen concentration of the river ranged from 1.84 - 162.8, 30.28 - 796.54 and 27.02 - 905.04 ?g/l, respectively. A decrease in the mean concentration of these parameters in monsoon was seen compared to their high concentration in pre-monsoon period, which however, increased again in post-monsoon and winter. In the one hand, strong positive correlation was observed between primary productivity and chl a, on the other hand, chl a showed strong positive correlation with phosphate-phosphorus and nitrate nitrogen. Significant negative correlation between dissolved oxygen (DO) and phosphate-phosphorus indicates the eutrophic nature of the river. This effect was minimized in monsoon. Concentration of phosphate-phosphorus, nitrate-nitrogen and chl a remained high in pre-monsoon period but reduced by 90, 87 and 97%, respectively in monsoon. Besides, DO recovered 90% in monsoon compared to its pre-monsoon concentration. Within a span of one and a half decade, the concentration of PO4-P and NO3-N in the water has increased 4 - and 32-fold, respectively. DOI: http://dx.doi.org/10.3329/bjb.v42i2.18031 Bangladesh J. Bot. 42(2): 287-294, 2013 (December)